A global view on stratospheric ice clouds: assessment of processes related to their occurrence based on satellite observations - L. Zou; S. Griessbach; L. Hoffmann; R. Spang (Atmospheric Chemistry and Physics, 2022)
Ice clouds play an important role in regulating water vapor and influencing the radiative budget in the atmosphere. This study investigates stratospheric ice clouds (SICs) in the latitude range between ±60∘<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="26pt" height="11pt" class="svg-formula" dspmath="mathimg" md5hash="3f386b3c4c65d74f8ea84f8ccc9562ae"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-22-6677-2022-ie00001.svg" width="26pt" height="11pt" src="acp-22-6677-2022-ie00001.png"/></svg:svg> based on the Cloud–Aerosol Lidar and Infrared Pathfinder Satellite Observations (CALIPSO). As polar stratospheric clouds include other particles, they are not discussed in this work. Tropopause temperature, double tropopauses, clouds in the upper troposphere and lower stratosphere (UTLS), gravity waves, and stratospheric aerosols are analyzed to investigate their relationships with the occurrence of and variability in SICs in the tropics and at midlatitudes.